(3WHbGJ GdCOHGAs - (3jGbhJ Hf YHO Gddg GdQhej GdMehj, TgGH GdOjf CHh YHO Gddg,J (B626 (3g` s
(3ChdgG (B:s
(3JQLeI YHOGddg Hf eMeO Hf CHj HQOI CHj eMeO s
(3BNQgG (B:s
(3JQLeI YeQ Hf HcjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B178s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B480 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B166 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(1103) s
Keywords: (3GdJGQjNs